Spexin: A novel candidate biomarker for differentiating diabetic cataract and cataract disease with diabetic retinopathy - Yardim, Meltem; Oruç, Ahmet Yavuz; Aydin, Suleyman (My University, 2019)
-
Keywords: Genel ve Dahili Tıp; Biyokimya ve Moleküler Biyoloji; İmmünoloji